2011
DOI: 10.1111/j.1467-629x.2011.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses by Australian auditors to the global financial crisis

Abstract: We examine the impact of the global financial crisis (GFC) on auditor behaviour in Australia. Using a sample of listed companies, we examine whether the GFC impacted the propensity of auditors to issue going concern modifications and increased audit effort as reflected in audit fees and audit reporting lag. Controlling for client characteristics, we find an increase in the propensity to issue going concern opinions during the period 2008-2009 compared with the period 2005-2007 and that Big N auditors responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
139
3
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 49 publications
12
139
3
12
Order By: Relevance
“…For example, there were three changes of Prime Minister between 2010 and 2013; see Smales (2015) for more details. 9 In contrast to the capital structure literature, there are more studies conducted during the GFC period in other areas, such as audit committee ; financial risk management (Ganegoda and Evans, 2014); superannuation investment choices (Gerrans, 2012); individual financial risk tolerance (Gerrans et al, 2015); banking (Akhtar and Jahromi, 2015); corporate governance (Adams, 2012); bank risk taking behaviour (Hoang, Faff, and Haq, 2014); trade credit (Kestens, Cauwenberge, and Bauwhede, 2012), bank regulation (Levine, 2012); and accounting areas (Mala and Chand, 2012;Xu et al, 2013). Having said that, there are two recent studies slightly related to the financial crisis by examining capital structure issues through business cycles (Akhtar, 2012;Liu and Chen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, there were three changes of Prime Minister between 2010 and 2013; see Smales (2015) for more details. 9 In contrast to the capital structure literature, there are more studies conducted during the GFC period in other areas, such as audit committee ; financial risk management (Ganegoda and Evans, 2014); superannuation investment choices (Gerrans, 2012); individual financial risk tolerance (Gerrans et al, 2015); banking (Akhtar and Jahromi, 2015); corporate governance (Adams, 2012); bank risk taking behaviour (Hoang, Faff, and Haq, 2014); trade credit (Kestens, Cauwenberge, and Bauwhede, 2012), bank regulation (Levine, 2012); and accounting areas (Mala and Chand, 2012;Xu et al, 2013). Having said that, there are two recent studies slightly related to the financial crisis by examining capital structure issues through business cycles (Akhtar, 2012;Liu and Chen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that companies who initiate clawbacks are perceived to have higher accounting quality and lower audit risk, as indicated by shorter ARL for these companies. Xu et al (2013) examined the performance of a sample of Australian companies from a macroeconomic perspective, evaluating auditor activity in response to the global financial crisis of 2008. They found that the financial crisis did appear to influence auditor effort and perception of risk.…”
Section: Performance and Financial Conditionmentioning
confidence: 99%
“…There are currently very few studies, either in Spain (Mareque, López-Corrales, & De Lima, 2012;Mareque, López-Corrales, & Pedrosa, 2011) or in other countries (Carson, Simnett, & Tronnes, 2011;Cheffers, Whalen, & Sielis, 2011;Cheffers, Whalen, & Thrun, 2010;Feldmann & Read, 2010;Jiang, 2013 and that show the effect of the financial crisis on audit reports. A recent review by Carson et al (2012) provides a synthesis of the existing academic literature on the presentation of reports containing problems of continuity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the rate of bankruptcies without prior issue of a going concern uncertainty opinion does not seem to have decreased notably during the period of financial crisis. Xu et al (2011Xu et al ( , 2013 published two papers on firms listed on the Australian stock exchange. In the first, they make a descriptive study for a sample of 8382 firms, in order to examine the response by Australian auditors to the current world financial crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation